Molecular authentication of crocodile dried food products (meat and feet) and skin sold on the Chinese market: Implication for the European market in the light of the new legislation on reptile meat. (June 2021) - Zhang, Xia; Armani, Andrea; Giusti, Alice; Wen, Jing; Fan, Sigang; Ying, Xiaoguo
Abstract: A molecular approach (DNA barcoding and phylogenetic analysis) using mitochondrial COI and 16SrRNA genes was used to identify species in crocodile dried food products (meat and feet) and skin sold on the Chinese market and generically labelled as "鳄鱼" (crocodiles). All the 80 collected samples (100%) were identified at species level and five of them were also identified at sub-species level using the COI gene. Limits of the DNA barcoding approach related to the presence of sequences from misidentified specimens on official genetic databases (Genbank and BOLD) were encountered. The only DNA barcoding method was successfully applied for the species identification of 47 (58.7%) samples (42 using the COI and 5 using the 16SrRNA ) while the support of the phylogenetic analysis was considered in 7 (8.7%) samples (performed using the 16SrRNA gene). For the remaining 26 samples (43.3%) the species identification was only achieved by phylogenetic analysis using the COI gene. Three species were overall detected: Crocodiles siamensis (n = 44; 55%), C. porosus (n = 29; 36.2%) and Caiman crocodilus (n = 7; 8.7%) with the sub-species C. crocodylus crocodylus in 5 out of the 7 cases. Although the traceability system of these products in China presented evident shortcomings, outcomes from this study appeared comforting since all the three species are among the most reared for meat production and can plausibly feed the market requests. Interestingly, only one of these species is included among those considered by the new EU legislation on reptile meat. Therefore, although Chinese crocodilian-based products are still not allowed to be imported in the EU market, a future law up-dating could not be excluded considering the relevance of the Chinese exports for the EU. Outcomes from this study, other than allowing to monitor products through the whole food value chain, contribute to enrich the scientific pool of data from which EU food imports legislation draw upon. Highlights: Crocodile species in Chinese food (meat and feet) and skin were molecularly verified. 100% of the samples were identified although limits of DNA barcoding were encountered. Crocodylus siamensis (55%), C. porosus (36.2%) and Caiman crocodilus (8.7%) were found. Only one species is currently allowed to be imported into EU among those detected. EU food imports legislation may draw upon from data obtained from this study.